FACTORS EFFECTING THE ADOPTING OF DIETARY DIVERSITY FORNUTRITIONAL SECURITY AMONG RURAL FARM WOMEN INWARANGAL, TELANGANA: A DESCRIPTIVE RESEARCH - KHUSHBOO YADAV, M. PREETHI, M. PRASUNA, APARNA KUNA, AMTUL WARIS; D. SRINIVASA CHARY (The Journal of Research, PJTSAU, 2026)
Dietary diversity served as a practical proxy for the micronutrient adequacy of diets consumed by rural farm women. The farm women remained disproportionately vulnerable to undernutrition despite its central role in agricultural production and household food provisioning. The present study was conducted among 30 rural farm women of reproductive age group (15 – 49 years) Warangal district village. The results revealed that majority of the respondents belonged from a selected village in (56.67%) middle age group followed by young (30.00%) and old (13.33%) age group. The category unveiled the respondents profile consisted of majority (43.33%) with Schedule caste followed by 33.33 per cent of OBC respondents and 16.67 per cent were from general category whereas only 6.67 per cent belonged to schedule tribes (ST) accounted the least. The family type of respondents belonged to nuclear (60.00%) and (40.00%) joint family type. While the factors affecting them to attain dietary diversity showed the economic constraints and agricultural as well as household work load hindered the most. Poor market assess, low decision making authority, poor nutritional knowledge and low livestock ownership were some more prominent contributors for their perceived constraints. The bottom most constraints ranked by the respondents were limited nutrition contact, limited homestead or kitchen garden followed by social norms and poor sanitation and unsafe water. The perceived constraints highlight the diverse yet important issues which rural women encounter in her highlighted life.